2020
DOI: 10.1007/s11136-020-02549-8
|View full text |Cite
|
Sign up to set email alerts
|

Using a quality of life (QoL)-monitor: preliminary results of a randomized trial in Dutch patients with early breast cancer

Abstract: Purpose The diagnosis and treatment of cancer negatively affect patients’ physical, functional and psychological wellbeing. Patients’ needs for care cannot be addressed unless they are recognized by healthcare providers (HCPs). The use of quality of life (QoL) assessments with feedback to HCPs might facilitate the identification and discussion of QoL-topics. Methods 113 patients with stage I–IIIB breast cancer treated with chemotherapy were included in this randomized controlled trial. Patients were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…We have previously shown in this trial that there were some small differences in reporting the items that were discussed between observers that evaluated the content of audio-recordings of consultations and patients who completed the questionnaires. 8 Regarding clinical practice implications, this study shows that despite the small differences in reporting psychosocial aspects of their disease and patient-physician communication, Japanese and Dutch patients are committed to participate in QoL-research. Modern oncology care in Japan is moving in the direction of what applies in Western societies, namely a focus on shared-decision making, QoL, self-management, patient-reported outcomes and patient-physician communication.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…We have previously shown in this trial that there were some small differences in reporting the items that were discussed between observers that evaluated the content of audio-recordings of consultations and patients who completed the questionnaires. 8 Regarding clinical practice implications, this study shows that despite the small differences in reporting psychosocial aspects of their disease and patient-physician communication, Japanese and Dutch patients are committed to participate in QoL-research. Modern oncology care in Japan is moving in the direction of what applies in Western societies, namely a focus on shared-decision making, QoL, self-management, patient-reported outcomes and patient-physician communication.…”
Section: Discussionmentioning
confidence: 82%
“…The detailed study design has been previously reported. 8 In brief, this open-label, multicentre study investigated the effects of introducing a QoL-monitor on aspects of communication, medical care and patient outcomes. The primary objective of this study was to assess the extent to which QoL-topics were discussed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations